Polyethylenimine-based nanocarriers in co-delivery of drug and gene: a developing horizon. (1st January 2018) - Zakeri, Abbas; Kouhbanani, Mohammad Amin Jadidi; Beheshtkhoo, Nasrin; Beigi, Vahid; Mousavi, Seyyed Mojtaba; Hashemi, Seyyed Ali Reza; Karimi Zade, Ayoob; Amani, Ali Mohammad; Savardashtaki, Amir; Mirzaei, Esmail; Jahandideh, Sara; Movahedpour, Ahmad
ABSTRACT: The meaning of gene therapy is the delivery of DNA or RNA to cells for the treatment or prevention of genetic disorders. The success rate of gene therapy depends on the progression and safe gene delivery system. The vectors available for gene therapy are divided into viral and non-viral systems. Viral vectors cause higher transmission efficiency and long gene expression, but they have major problems, such as immunogenicity, carcinogenicity, the inability to transfer large size genes and high costs. Non-viral gene transfer vectors have attracted more attention because they exhibit less toxicity and the ability to transfer large size genes. However, the clinical application of non-viral methods still faces some limitations, including low transmission efficiency and poor gene expression. In recent years, numerous methods and gene-carriers have been developed to improve gene transfer efficiency. The use of Polyethylenimine (PEI) based transfer of collaboration may create a new way of treating diseases and the combination of chemotherapy and gene therapy. The purpose of this paper is to introduce the PEI as an appropriate vector for the effective gene delivery.